al-Darūrāt al-‘Ilmiyyah wa al-Tarbawiyyah li-Tadrīs al-Sīrah al-Nabawiyyah fī al-Mu’assasāt al-Ta‘līmiyyah - Ahmad al-Shash, Hidayatullah (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2025)
This study highlights the state of contemporary education in Muslim societies, which has fallen short in protecting the Islamic identity of the younger generation and weakening their sense of belonging. This decline stems from the marginalization of religious education and its replacement with secular systems that confine learning to a narrow material framework. Hence, this research underscores the scientific and pedagogical necessity of teaching the Prophetic Biography, revealing its role and benefits in shaping a balanced Islamic personality. Using an analytical inductive method, the study concludes that integrating religious education—particularly the Prophetic Biography—into all curricula is essential for nurturing generations upon Islam’s comprehensive worldview. It demonstrates that teaching the Prophet’s life is not mere historical narration but a holistic educational process that instills values, builds moral exemplars, and strengthens awareness of Islamic identity. The research recommends renewing methods of teaching the Prophetic Biography through engaging educational storytelling that presents it as a living model, enabling students to interact with its figures and emulate their commitment to faith and society.